Ethnic differences in selective neonatal BCG immunisation: white British children miss out. Issue 3 (29th December 2005) - Srinivasan, R; Menon, L; Stevens, P; Campbell, I; Alfaham, M
Abstract : Background: Tuberculosis (TB) is a re-emerging problem, especially in the larger cities of Western Europe. Selective neonatal BCG vaccination is recommended for infants at risk of TB in the UK. Neonatal BCG is safe and effective, with an overall protective value of 75%. This study aimed to assess BCG rates among at risk infants in Cardiff and the Vale of Glamorgan, South Wales in the year 2003. Methods: A cohort of infants at risk for TB was identified from demographic data stored on a computerised maternity activity database. A manual search of immunisation records determined overall rates and the rates for infants belonging to various ethnic groups. Results: Of 5308 infants born in 2003, 514 (9.6%) were at risk of TB; 423 (82.2%) of these infants were referred postnatally for BCG vaccination and 391 received it. Twenty six of the 41 at risk white British infants missed having a BCG vaccination compared with 47 of 288 Asian infants and seven of 39 black African babies. The rate of BCG vaccination among white British infants was 36.5% compared with 83.6% for Asian infants from the Indian subcontinent (χ 2  = 7.25, p<0.01) and 82% for black African infants (χ 2  = 4.48, p<0.05). Conclusions: The overall BCG rate among at risk infants in Cardiff was 76% during the study period. The vaccination rate was poor among white British infants compared with other ethnic groups. Enhanced awareness of health professionals to recognise the need for vaccinating certain white children at risk of TB is essential to improve BCG coverage in an increasingly multiethnic population.